The role of T-cells in head and neck squamous cell carcinoma: From immunity to immunotherapy - Damasio, Marcos Paulo S.; Nascimento, Camila Sales; Andrade, Lidia M.; de Oliveira, Vivian L.; Calzavara-Silva, Carlos Eduardo (Frontiers in Oncology, 2022)
Head and neck squamous cell carcinoma (HNSCC) encompass a group of complex entities of tumours affecting the aerodigestive upper tract. The main risk factors are strongly related to tobacco and alcohol consumption, but also HPV infection is often associated. Surgery, radiotherapy and/or chemotherapy are the standard treatments, though the 5-year overall survival is less than 50%. The advances in genomics, molecular medicine, immunology, and nanotechnology have shed a light on tumour biology which helps clinical researchers to obtain more efficacious and less toxic therapies. Head and neck tumours possess different immune escape mechanisms including diminishing the immune response through modulating immune checkpoints, in addition to the recruitment and differentiation of suppressive immune cells. The insights into the HNSCC biology and its strong interaction with the tumour microenvironment highlights the role of immunomodulating agents. Recently, the knowledge of the immunological features of these tumours has paved the way for the discovery of effective biomarkers that allow a better selection of patients with odds of improving overall survival through immunotherapy. Specially biomarkers regarding immune checkpoint inhibitors antibodies, such as anti-PD-1/PD-L1 and anti-CTLA-4 in combination with standard therapy or as monotherapy. New immunotherapies to treat head and neck cancer carcinomas, such as CAR T cells and nanoparticles have been the center of attention and in this review, we discuss the necessity of finding targets for the T cell in the cancer cells to generate CAR T cells, but also the relevance of evaluating specificity and safety of those therapies.